Thursday

April 17, 2014

April 17, 2014

Posted by **george** on Thursday, January 14, 2010 at 5:11pm.

1. 2m - 1 = 3m subtract m

2. 2m = 1 + m subtract 2

3. m - 1 = 2 subtract 1

4. 2 + m = 3 subtract 2m

5. -2 + m = 1 add 2

6. 3 = 1 + m add 1

- math -
**drwls**, Thursday, January 14, 2010 at 5:15pmTry the various operations

Only #5 will leave you with an equation for m

**Related Questions**

math - Match the equation with the step needed to solve it. 1. 2m - 1 = 3m ...

math ALGEBRA - Solve by either the substitution method or the addition or ...

algebra - 2m-1=3m what is the first step needed to solve this

MATH PLEASE CHECK IT!!2 - m-2/m-5*m+5/m-2=-1 If your problem is this: (m - 2)/(m...

Math - This irregular shape has 2m,2m,2m, 3m, 4m, 7m _2m_ _2m_ | |2m__3m_...

algebra - Here is the problem I am working on and what I did so far: 4+m-3m ...

maths - What would the equation be of a straight line that passes through the ...

calculus - A conical tank has height 3m and radius 2m at the top. Water flows in...

MATH - Which of the following equations has the given solution set? Solution set...

math - what expression can be used to represent the phrase "3 more than 2 times ...